Dyslipidemia and endothelial function in women with metabolic syndrome associated with autoimmune thyroiditis - N. S. Kanavets; L. I. Levina; V. V. Popov; N. Ph. Priyma; A. B. Shapovalova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2014)
The research objectives are lipid spectrum and endothelial function (EF) in women with metabolic syndrome (MS) associated with autoimmune thyroiditis (AIT) against the background of non-compensated with L-thyroxin subclinical hypothyroidism (SH). Groups of women with MS associated with AIT and euthyroidism, women with MS associated with SH and women with MS without any thyroid disorders were observed. Complex «intima media» and endothelial function of brachial artery were evaluated by ultrasound method. It was indicated that dyslipidemia was more significant in women with MS associated with AIT and SH. But there were no abnormalities in complex «intima media» and EF. The cause of it is that the diabetes mellitus occurred two times rarely in this group in comparison with the other groups as well as the high sensitivity to the L-thyroxin. The results of the study demonstrate the necessary prescription of adequate dose of L-thyroxin to compensate SH completely.